Management of Bloodstream Infections in Left Ventricular Assist Device Recipients: To Suppress, or Not to Suppress?. (16th November 2020) - Esquer Garrigos, Zerelda; Jandhyala, Deeksha; Vijayvargiya, Prakhar; Castillo Almeida, Natalia E; Gurram, Pooja; Corsini Campioli, Cristina G; Stulak, John M; Rizza, Stacey A; O'Horo, John C; DeSimone, Daniel C; Baddour, Larry M; Sohail, M Rizwan
Abstract: Background: Ascertaining involvement of left ventricular assist device (LVAD) in a patient presenting with bloodstream infection (BSI) can be challenging, frequently leading to use of chronic antimicrobial suppressive (CAS) therapy. We aimed to assess the efficacy of CAS therapy to prevent relapse of BSI from LVAD and non-LVAD sources. Methods: We retrospectively screened adults receiving LVAD support from 2010 through 2018, to identify cases of BSI. Bloodstream infection events were classified into LVAD-related, LVAD-associated, and non-LVAD BSIs. Results: A total of 121 episodes of BSI were identified in 80 patients. Of these, 35 cases in the LVAD-related, 14 in the LVAD-associated, and 46 in the non-LVAD BSI groups completed the recommended initial course of therapy and were evaluated for CAS therapy. Chronic antimicrobial suppressive therapy was prescribed in most of the LVAD-related BSI cases (32 of 35, 91.4%) and 12 (37.5%) experienced relapse. Chronic antimicrobial suppressive therapy was not prescribed in a majority of non-LVAD BSI cases (33, 58.9%), and most (31, 93.9%) did not experience relapse. Chronic antimicrobial suppressive therapy was prescribed in 9 of 14 (64.2%) cases of LVAD-associated BSI and none experienced relapse. Of the 5 cases in this group that were managed without CAS, 2 had relapse. Conclusions: Patients presenting with LVAD-related BSI are at high risk of relapse. Consequently, CAS therapy may be a reasonable approach in the management of these cases. In contrast, routine use of CAS therapy may be unnecessary for non-LVAD BSIs. Abstract : Routine use of CAS therapy may be unnecessary for cases of non-LVAD BSIs. In contrast, CAS therapy seems a reasonable approach to prevent relapse of BSI in LVAD-related cases.